Menciptakan Teknopreneur Muda Bidang Jasa Service R-HVAC Di Politeknik Negeri Indramayu - yudhy kurniawan; Wardika (ISAS (Indonesian Society of Applied Science), 2021)
One of the big problems in Indramayu regency is that there is still a large number of unemployed, especially from school and college graduates, while the demands of the need or availability of skilled workers in the industry have not been able to absorb the results of these graduates. Based on data from BAPPEDA in Indramayu regency, the labor force data three years earlier has reached 782,856 around 63.25% is TPAK (Labor Force Unemployment Rate). Answering the important problem above, there needs to be concrete efforts of Polytechnic State of Indramayu (POLINDRA) in realizing Tri Darma Perguruan Tinggi, namely Community Service Activities (PKM), in this case conducting an entrepreneurial program for Polindra graduates by creating a service unit in the field of Refrigerating and Air Conditioning (R-HVAC) to help overcome productive labor unemployment. The purpose of this PKM is to produce competent young educated technopreneurs in the field of R-HVAC who are able to work independently in order to improve the standard of living and reduce the number of unemployed productive age, especially in the Indramayu regency. This program is conducted by involving graduate students, especially those majoring in Refrigeration and Air Conditioning who have entrepreneur interests and have competence in their fields. Then they are educated their knowledge and skills, entrepreneur insights and work ethic, so that when running a business can be done professionally and responsibly.